أثر استخدام استراتيجية التعلم المستقل في تنمية مهارة فهم المقروء لدى الطالبات من القسم الإعدادي بجامعة الراية - WIDIAS HAPSARI; ARIF TAUFIQURRAHMAN (Lembaga Penelitian dan Pengabdian Masyarakat, Sekolah Tinggi Ilmu Bahasa Arab Ar Raayah, 2016)
The study aimed at uncovering the impact of the independent learning strategy in developing reading comprehension skill among the students of the second semester of the STIBA at Ar-Raayah. This study used quantitative research and experimental method. In order to achieve the objectives of the study, the researcher applies a reading comprehension test technique that examines reading skills, among others: Literal understanding skills (mahārati fahmi al-harfy), deductive understanding skills (mahārati fahmi al-istintāji), critical understanding skills (mahārati fahmi an-naqdi), language comprehension skills (mahārati fahmi tadzuki), the skill of understanding epistemology (mahārati fahmi al-ibdāi). Tests were performed in the reading comprehension technique in order to understand that the difference between the experimental group and the control group. The study was a sample of to second semester studends consisting of 30 fermale students. The sample of the study was distributed to a group 15 of students who studied the strategy on independent learning, and experimental a group consises 15 students studied according to the traditional method. The study reached the following result: The use of the independent learning strategy has an impact on the development of reading comprehension skill in STIBA Ar-Raayah. Tidentify the basic strategy that should be taken into consideration when preparing educational activities aimed at developing reading compreension skill